2007
DOI: 10.1016/j.jtcvs.2007.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors affecting outcome and morbidity in the surgical management of bronchiectasis

Abstract: A history of tuberculosis and incomplete resection were risk factors both for postoperative complications and for a worse operative result. The lack of a preoperative bronchoscopic examination and a low forced expiratory volume in 1 second were risk factors for postoperative complications. Surgery for multiple segments on different lobes should be performed whenever possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 23 publications
5
46
1
5
Order By: Relevance
“…The experience reported here is especially relevant in light of a number of recent studies reinforcing a role for the surgical management of bronchiectasis, particularly for localized lesions [12][13][14][15]. The role of surgery for patients with non-NTM associated bronchiectasis parallels that for pulmonary NTM patients: to eliminate damaged segments or lobes contributing to overwhelming secretions, to eliminate sources of hemoptysis, and to remove damaged lung suspected of harboring problematic organisms [16].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The experience reported here is especially relevant in light of a number of recent studies reinforcing a role for the surgical management of bronchiectasis, particularly for localized lesions [12][13][14][15]. The role of surgery for patients with non-NTM associated bronchiectasis parallels that for pulmonary NTM patients: to eliminate damaged segments or lobes contributing to overwhelming secretions, to eliminate sources of hemoptysis, and to remove damaged lung suspected of harboring problematic organisms [16].…”
Section: Discussionmentioning
confidence: 83%
“…The role of surgery for patients with non-NTM associated bronchiectasis parallels that for pulmonary NTM patients: to eliminate damaged segments or lobes contributing to overwhelming secretions, to eliminate sources of hemoptysis, and to remove damaged lung suspected of harboring problematic organisms [16]. Recent studies, including a 790-patient cohort by Zhang et al [15] used primarily an open approach to resection and reported symptom improvement for 70-98% or more of patients treated [12][13][14][15]. Morbidity ranged from 11% to 23% and mortality ranged from 0% to 1.7%.…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients do not experience any etiologic factor. [8][9][10][11] Some have underlying diseases like cystic fi brosis, requiring that surgical procedures be chosen carefully to prevent complications and mortality. 12 The percentage of recurrent pulmonary infections starting from childhood was 21%, and the percentage of patients who did not have any etiologic factors was 26%.…”
Section: Discussionmentioning
confidence: 99%
“…As bronchiectasis has an inflammatory basis, surgical treatment of the disease carries a considerable increased risk in both pre and postoperative periods [7,8]. Current mortality rates, ranging from 1 to 9%, are reported to be declining by virtue of advanced surgical care [2][3][4][9][10][11][12].…”
Section: Espite Improvements In Medication and Equipmentmentioning
confidence: 99%
“…However, few reports have particularly focused on the prediction of postoperative morbidity by using preoperative measures [7,8]. In this study, we present our seven-year experience with a special focus on the influence of some specific factors on postoperative morbidity on young adult patients who were treated surgically with the diagnosis of bronchiectasis.…”
Section: Espite Improvements In Medication and Equipmentmentioning
confidence: 99%